2020
DOI: 10.1104/pp.20.01219
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylglycerol Composition Is Central to Chilling Damage in the Arabidopsis fab1 Mutant

Abstract: Arabidopsis fab1 mutants die at 2°C; however, reducing levels of high-melting-point phosphatidylglycerol species through expression of a chloroplast-targeted 16:0 desaturase rescues fab1 plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Finally, 16:0-ACP is elongated by KASII to 18:0-ACP and then desaturated by SAD to generate 18:1-ACP (Lindqvist et al, 1996;Carlsson et al, 2002). The content of C16:0 in Arabidopsis KASII mutant (kas2) was remarkably increased (Gao et al, 2020), whereas the decreased activity of AAD5 resulted in a significant reduction in the level of C18:1 in mature seeds (Kazaz et al, 2020). Thus, the decrease of AtAAD5 expression led to the reduction of C18:1 in transgenic Arabidopsis, while the upregulation of PrSAD and PrKASII increased the C18:0 and C18:1 in PrASIL1-silenced tree peony.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 16:0-ACP is elongated by KASII to 18:0-ACP and then desaturated by SAD to generate 18:1-ACP (Lindqvist et al, 1996;Carlsson et al, 2002). The content of C16:0 in Arabidopsis KASII mutant (kas2) was remarkably increased (Gao et al, 2020), whereas the decreased activity of AAD5 resulted in a significant reduction in the level of C18:1 in mature seeds (Kazaz et al, 2020). Thus, the decrease of AtAAD5 expression led to the reduction of C18:1 in transgenic Arabidopsis, while the upregulation of PrSAD and PrKASII increased the C18:0 and C18:1 in PrASIL1-silenced tree peony.…”
Section: Discussionmentioning
confidence: 99%
“…KAS2, also known as fatty acid biosynthesis1 (fab1), has a degree of 3082 in this network. The fab1 mutant has increased levels of the saturated fatty acid 16:0, resulting in embryo arrest at the early embryo development stage [ 26 ]. Plastidic pyruvate kinase (PKPs) catalyze the synthesis of pyruvate and ATP; PKP1 and PKP2 have degrees of 3042 and 3038 in this network, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, 82 seed development or embryo development-related genes are enriched in our MElightgreen module. Previous studies have shown that some of these genes regulate seed development in Arabidopsis, including Fatty Acid Biosynthesis1 ( KAS2/FAB1 ) [ 26 ], plastidic pyruvate kinase PKP1 and PKP2 [ 27 ], NF-YA family member6 ( NFYA6 ) [ 45 ], carboxypeptidase ALTERED MERISTEM PROGRAM 1 ( AMP1 ) [ 46 ], β-Ketoacyl-[acyl carrier protein] synthase I ( KASI ) [ 44 ], and the homeobox genes MERISTEM LAYER1 ( ATML1 ) and PROTODERMAL FACTOR2 ( PDF2 ) [ 47 ]. These genes have many degrees in the MElightgreen module co-expression network ( Figure 6 D).…”
Section: Discussionmentioning
confidence: 99%
“…The exact reasons for these marked effects are not clear, but it was shown that changes in the composition of membrane lipids, induced by modifications of different lipid biosynthesis genes, affect photosynthetic properties (Botté et al, 2011; Kobayashi, 2016; Gao et al, 2020). Thus, it seems conceivable that the altered chloroplast membrane composition observed in FAX1 overexpressors (Supplemental Figure 1 and Figure 8) is causative for the impaired photosynthetic performance.…”
Section: Discussionmentioning
confidence: 99%